FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN ASET PERUSAHAAN ASURANSI JIWA NON SYARIAH DI INDONESIA - Istianingsih Sastrodiharjo; I Putu Sutama (Akuntabilitas, 2015)
The development of life insurance in Indonesia is quite slow compared to otherfinancial industry. This study was conducted to examine the factors that influence the growthof asset of non-life insurance shariah company in Indonesia for the period 2004 to 2010. Thevariables tested are premium growth, capital growth, returns, claims ratio, the ratio ofacquisition costs, the cost ratio administration, the type of capital, and the amount of capital.The sample used in this study is a life insurance company during the study period of 2004 to2010. The data analysis technique used is multiple linear regressions. The results of theanalysis prove that premium growth, capital growth, returns, claims ratios, and types ofcapital affect the growth of the life insurance company's assets. While the acquisition costratio, the ratio of administrative costs and the amount of capital do not significantly influencethe growth of assets of life insurance companies in IndonesiaDOI: 10.15408/akt.v8i1.2759